Factores de no adherencia al tratamiento en personas con Diabetes Mellitus tipo 2 en el domicilio. La visión del cuidador familiar (2011)
ABSTRACT: To understand the non adherence factors to treatment of people with type 2 Diabetes Mellitus (DM2) from the family caregiver’s view. Methodology. Ethnographic study performed in 2008. 18 interviews to type 2 DM patient’s caregivers who belonged to diabetes control programs from healthcare institutions of the city of Medellin (Colombia) were conducted. Six observations of significant moments of care were also made. Results. Treatment adherence in people with type 2 DM is mediated by multiple factors that difficult it, as: Cultural beliefs of the disease, disagreement between healthcare professionals and popular knowledge, tiredness of taking that many medicines, fear of multiple punctures for insulin application, dissatisfaction with healthcare services and the long term cost of the disease. Conclusion. From the family caregiver’s view, treatment adherence of people with type 2 DM is low as a consequence of multiple factors which influence it.